Sweatlodge in the Apocalypse: A Conversation with Smokii Sumac : James Mackay - Mackay, James (Transmotion, 2020)
Ktunaxa poet-scholar Smokii Sumac's first book of poetry, you are enough: love poems for the end of the world, was published by Kegedonce in 2018, and won the Indigenous Voices Award. Here he talks with Transmotion editor James Mackay.